2005
DOI: 10.4049/jimmunol.174.12.7912
|View full text |Cite
|
Sign up to set email alerts
|

B Lymphocyte Activation by Human Papillomavirus-Like Particles Directly Induces Ig Class Switch Recombination via TLR4-MyD88

Abstract: Vaccination with human papillomavirus type 16 (HPV16) L1 virus-like particles (VLP) induces both high titer neutralizing IgG and protective immunity. Because protection from experimental infection by papillomavirus is mediated by neutralizing IgG, we sought the mechanisms that trigger humoral immunity to HPV16 L1 VLP. We find that HPV16 L1 VLP bind to murine B lymphocytes thereby inducing activation-induced cytidine deaminase expression and Ig class switch recombination to cause the generation of IgG. HPV16 L1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
54
1
1

Year Published

2006
2006
2011
2011

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(62 citation statements)
references
References 70 publications
6
54
1
1
Order By: Relevance
“…HPV16 VLPs, for example, can directly activate B cells in a TLR4-dependent manner to induce CD4 ϩ T cell-independent class switching (16). In contrast, our data show that T help is strictly required for the induction of both anti-self and anti-foreign Abs by VLP-HEL.…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…HPV16 VLPs, for example, can directly activate B cells in a TLR4-dependent manner to induce CD4 ϩ T cell-independent class switching (16). In contrast, our data show that T help is strictly required for the induction of both anti-self and anti-foreign Abs by VLP-HEL.…”
Section: Discussioncontrasting
confidence: 51%
“…However, some multivalent Ags, including papillomavirus VLPs, are able to activate B cells and induce class switching in the absence of T help (16). In this regard, T-independent responses to pathogens and autoantibody responses to conjugated VLPs are promoted by similar repetitive antigenic structures and are perhaps dependent on similar stringent requirements for Ag-induced crosslinking of BCRs (15,17,18).…”
mentioning
confidence: 99%
“…QARVLAVERY elicits significantly higher IgA than does ELDKWA independent of the vector-delivery regimen Recent evidence has suggested that factors such as mucosal delivery of antigens, 58 use of adjuvants, 59,60 certain viral antigens, 61,62 or VLP administration 63,64 may influence IgA induction and can directly or indirectly modulate Ab class-switch recombination. Here, we determined whether the significantly higher IgA generated against QARVLAVERY was a property of the epitope alone, independent of such factors in our immunization model.…”
Section: Articlesmentioning
confidence: 99%
“…HPV L1 VLPs have been reported elsewhere to induce cytokine response in DCs, monocytes, and macrophages (41)(42)(43), possibly in a TLR-dependent fashion (44,45). Abs against HPV L1 VLPs were found to be reduced in TLR4-deficient mice by Yang et al (44) but not by others (46).…”
Section: Crucial Role Of Mpl In As04 For the Stimulation Of An Innatementioning
confidence: 95%